Angiogenesis blockade as a new therapeutic approach to experimental colitis. Issue 6 (14th December 2006) - Danese, Silvio; Sans, Miquel; Spencer, David M; Beck, Ivy; Doñate, Fernando; Plunkett, Marian L; de la Motte, Carol; Redline, Raymond; Shaw, David E; Levine, Alan D; Mazar, Andrew P; Fiocchi, Claudio
Abstract : Background: Neoangiogenesis is a critical component of chronic inflammatory disorders. Inhibition of angiogenesis is an effective treatment in animal models of inflammation, but has not been tested in experimental colitis. Aim: To investigate the effect of ATN-161, an anti-angiogenic compound, on the course of experimental murine colitis. Method: Interleukin 10-deficient (IL10 −/− ) mice and wild-type mice were kept in ultra-barrier facilities (UBF) or conventional housing, and used for experimental conditions. Dextran sodium sulphate (DSS)-treated mice were used as a model of acute colitis. Mice were treated with ATN-161 or its scrambled peptide ATN-163. Mucosal neoangiogenesis and mean vascular density (MVD) were assessed by CD31 staining. A Disease Activity Index (DAI) was determined, and the severity of colitis was determined by a histological score. Colonic cytokine production was measured by ELISA, and lamina propria mononuclear cell proliferation by thymidine incorporation. Result: MVD increased in parallel with disease progression in IL10 −/− mice kept in conventional housing, but not in IL10 −/− mice kept in UBF. Angiogenesis also occurred in DSS-treated animals. IL10 −/− mice with established disease treated with ATN-161, but not with ATN-163, showed a significant and progressive decrease in DAI. The histological colitis score was significantly lower in ATN-161-treated mice than in scrambled peptide-treated mice. Inhibition of angiogenesis was confirmed by a significant decrease of MVD in ATN-161-treated mice than in ATN-163-treated mice. No therapeutic effects were observed in the DSS model of colitis. ATN-161 showed no direct immunomodulatory activity in vitro. Conclusion: Active angiogenesis occurs in the gut of IL10 −/− and DSS-treated colitic mice and parallels disease progression. ATN-161 effectively decreases angiogenesis as well as clinical severity and histological inflammation in IL10 −/− mice but not in the DDS model of inflammatory bowel disease (IBD). The results provide the rational basis for considering anti-angiogenic strategies in the treatment of IBD in humans.